Integrating the arts across the elementary school curriculum - Gelineau, R. Phyllis (Wadsworth/Cengage Learning, 2012)
"This book is designed to assist pre-service and in-service classroom teachers in weaving music, visual arts, drama, and movement into the elementary school curriculum--thereby stimulating the learning process, enriching other subject areas, and providing opportunities for creative expression and self-fulfillment. Featuring content informed by the National Standards for the Arts, the book provides the basic tools and activities that teachers need to gain confidence in using the arts in their elementary classrooms."--Publisher's description.